2018
DOI: 10.3390/ijms19092594
|View full text |Cite
|
Sign up to set email alerts
|

Th1-Biased Immunomodulation and In Vivo Antitumor Effect of a Novel Piperine Analogue

Abstract: Natural products have an important role as prototypes in the synthesis of new anticancer drugs. Piperine is an alkaloid amide with antitumor activity and significant toxicity. Then, the N-(p-nitrophenyl)acetamide piperinoate (HE-02) was synthesized, and tested for toxicological and antitumor effects. The toxicity was evaluated in vitro (on RAW 264.7 cells and mice erythrocytes) and in vivo (acute toxicity in mice). The Ehrlich ascites carcinoma model was used to evaluate the antitumor activity of HE-02 (6.25, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Similarly, piperine exhibited positive effects against cadmium‐induced oxidative stress in cultured human peripheral blood lymphocytes (Verma, Bal, Gupta, Aggarwal, & Yadav, 2018). Furthermore, research by Santos and coworkers showed that the piperine analogue, N‐( p ‐nitrophenyl)acetamide piperinoate, exhibits low toxicity and shows antitumor effects by Th1‐based immunomodulation (Santos et al, 2018). Moreover, Kumar et al (2015) indicated that piperine enhances antioxidant function by prevention of glutathione depletion and restoration of cytokine levels.…”
Section: Health Perspectivesmentioning
confidence: 99%
“…Similarly, piperine exhibited positive effects against cadmium‐induced oxidative stress in cultured human peripheral blood lymphocytes (Verma, Bal, Gupta, Aggarwal, & Yadav, 2018). Furthermore, research by Santos and coworkers showed that the piperine analogue, N‐( p ‐nitrophenyl)acetamide piperinoate, exhibits low toxicity and shows antitumor effects by Th1‐based immunomodulation (Santos et al, 2018). Moreover, Kumar et al (2015) indicated that piperine enhances antioxidant function by prevention of glutathione depletion and restoration of cytokine levels.…”
Section: Health Perspectivesmentioning
confidence: 99%
“…Then, the AMTAC-17 effect on microvessels density may be dependent on IL-12 antiangiogenic action. Additionally, IL-12, IL-1β, and TNF-α represent the Th1 cytokines profile, which is known for the cytotoxic effect against cancer cells [22,23]. This effect involves macrophage activation to secrete proinflammatory cytokines and produce reactive oxygen species and nitric oxide [24].…”
Section: Biological Evaluationmentioning
confidence: 99%
“…Cells from ascitic fluid (1 × 10 6 cells) of the tumor control, 12.5 mg/kg AMTAC-17, and 25 mg/kg 5-FU groups were harvested, gently fixed by using 70% ice-cold ethanol, and frozen overnight (−20 • C). Samples were harvested by centrifugation (400× g, 10 min), and then incubated with RNAse (0.1 mg/mL) and propidium iodide (PI) (0.05 mg/mL) (Sigma Aldrich, St. Louis, MO, USA) (37 • C, 30 min) [22] with modifications. The DNA content was analyzed by flow cytometry (BD FACSCantoTM II, Woburn, MA, USA) and 10,000 events were acquired.…”
Section: Cell Cycle Analysesmentioning
confidence: 99%
“…The volume of ascitic fluid was collected from the peritoneal cavity to determine the tumor volume (mL). Trypan blue assay was used to evaluate the cell viability [51].…”
Section: Evaluation Of In Vivo Antitumor Activity In the Ehrlich Ascimentioning
confidence: 99%
“…Concentrations of nitrite were calculated from a standard curve previously established with known molar concentrations of sodium nitrite. The tests were done in quadruplicate and the values expressed in µM [51].…”
Section: Quantification Of Nitrite Levels In the Ehrlich Ascites Carcmentioning
confidence: 99%